2015
DOI: 10.1111/aab.12243
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen or potassium preconditioning affects uptake of both nitrate and potassium in young wheat (Triticum aestivum)

Abstract: Plant uptake rates of nitrate and potassium (K) are under feedback control from plant concentrations of nitrogen (N) and K, respectively. However, there is uncertainty concerning the interactions between nitrate and K uptake. We tested the hypothesis that plant concentrations of N affect K uptake and plant concentrations of K affect uptake rates of nitrate. Two experiments were carried out with wheat. Each consisted of three phases. In Phase 1, the plants were grown in complete nutrient solution for 17-18 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The Mechanisms Modulating Foliar K Level Under Nitrate Starvation K + and nitrate were shown to reciprocally facilitate each other's uptake, and nitrate starvation decreased K + uptake (Ivashikina and Feyziev, 1998;Lu et al, 2005;Reid et al, 2016). These reports are in accordance with our results (Supplemental Figure 6C and 6F).…”
Section: Nrt15 Modulates Foliar K + Level To Suppress Nitrate Starvation-initiated Leaf Senescencesupporting
confidence: 91%
“…The Mechanisms Modulating Foliar K Level Under Nitrate Starvation K + and nitrate were shown to reciprocally facilitate each other's uptake, and nitrate starvation decreased K + uptake (Ivashikina and Feyziev, 1998;Lu et al, 2005;Reid et al, 2016). These reports are in accordance with our results (Supplemental Figure 6C and 6F).…”
Section: Nrt15 Modulates Foliar K + Level To Suppress Nitrate Starvation-initiated Leaf Senescencesupporting
confidence: 91%
“…Increasing K fertilizer instead of N in reference to a suitable N/K value caused no marked change in g tot and V cmax or A n , confirming previous studies that excessive K cannot continually boost CO 2 transport ability (O'Toole et al , Jin et al , Lu et al ) and Rubisco activity (Weng et al ). Leaf photosynthetic capacity would not be increased effectively by elevating K nutrition to a threshold value, which is more pronounced under sufficient N nutrition (Reid et al ). As mesophyll conductance and Rubisco contents in leaves are heightened with the increases in N supply (Ghannoum et al , Li et al ), g tot and V cmanx values were higher with increasing N nutrition, as opposed to K, in reference to a suitable N/K ratio.…”
Section: Discussionmentioning
confidence: 99%
“…activity (Weng et al 2007). Leaf photosynthetic capacity would not be increased effectively by elevating K nutrition to a threshold value, which is more pronounced under sufficient N nutrition (Reid et al 2016). As mesophyll conductance and Rubisco contents in leaves are heightened with the increases in N supply (Ghannoum et al 2005, g tot and V cmanx values were higher with increasing N nutrition, as opposed to K, in reference to a suitable N/K ratio.…”
Section: Figmentioning
confidence: 94%
“…The response of plants to one nutrient is very dependent on the availability status of other nutrients. Several studies have shown that sufficient potassium nutrients will significantly increase the absorption and utilization of N and P by plants [14] as well as increase the response rate of N and P fertilizer utilization [15]. The application of K fertilizer also increases carbohydrate and N metabolism and therefore increases the quality of plant products [16].…”
Section: Discussionmentioning
confidence: 99%